Microstructure evolution and pitting corrosion behavior of UNS S32750 super duplex stainless steel welds after short-time heat treatment. (June 2017) - Zhang, Ziying; Zhao, Hui; Zhang, Huizhen; Hu, Jun; Jin, Jiarui
Highlights: The microstructure of the as-welded HAZ deviated far from the equilibrium state. The ferrite phase in the as-welded HAZ was the weaker phase. The evolution of pit site versus heat treatment temperature was discussed. The optimum shot-time heat treatment temperature was determined. Abstract: The effects of short-time heat treatment at different temperatures on the microstructure evolution and pitting corrosion behavior of UNS S32750 super duplex stainless steel welds were investigated. The results demonstrated that the ferrite phase in the as-welded heat-affected zone overwhelmed the austenite phase in content and was easily attacked by pitting corrosion. After short-time heat treatment, the excessive ferritization in the heat-affected zone was significantly alleviated. The highest pitting corrosion resistance of the welds was obtained at 1080 °C.